The Effect of Dexmedetomidine on Mortality in Patients with Acute Pancreatitis: A Retrospective Propensity Score Matching Analysis - Zhang, Hui; Wang, Hui-juan; Tang, Wen-jing; Wu, Yun-long (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Acute pancreatitis (AP) is a prevalent gastrointestinal disorder, with its frequency rising annually, and the fatality rate in severe cases reaching 38%. Dexmedetomidine (DEX), possessing analgesic, sedative, anti-inflammatory, and anti-sympathetic properties, appears to be a viable pharmacological option for AP; however, the clinical correlation remains ambiguous. This study aimed to elucidate the potential of DEX in enhancing the prognosis of patients with AP. Materials and Methods: The Medical Information Mart for Intensive Care–IV database served as the foundation for this retrospective propensity score-matched cohort analysis. Participants with AP diagnoses were split into 2 groups according to whether they received DEX for the study. Propensity score matching (PSM) was used to align the baseline data for the 2 groups. A multivariate Cox propor tional hazards regression model and Kaplan–Meier survival curves were used to assess the relationship between DEX treatment and the 60-day death rate in patients with AP. Subgroup analyses were undertaken to ensure the reliability of the findings. Results: There were 362 patients in this test period, 181 of whom were in the DEX group and 181 of whom were in the No-DEX group. The standardized mean differences of all baseline features were less than 0.1, and the P-value was greater than .05 after the PSM of the baseline data of the 2 patient groups. This suggests that the 2 patient groups were well-balanced following matching. The 2 groups’ 60-day mortality rates differed significantly, according to the Kaplan–Meier survival curve. The DEX group’s survival rate was higher than the No-DEX group’s at the same time point (hazard ratio [HR] (95% CI) = 0.048 (0.406-1.002), P = .048). To evaluate the effect of DEX on mortality in AP patients, multiple Cox regression models that adjusted for different factors were used. According to the fully adjusted model, DEX improves the prognosis of patients with AP. The HR for 60-day death in the matched group was 0.51 (95% CI: 0.30-0.88), P = .015. Conclusion: The current study revealed that DEX administration can decrease the 60-day death rate in individuals with AP. Nonetheless, the verification of this claim necessitates multicenter randomized controlled trials. Zhang H, Wang H, Tang W, Wu Y. The effect of dexmedetomidine on mortality in patients with acute pancreatitis: a retrospective propensity score matching analysis. Turk J Gastroenterol. Published online November 11, 2025. doi:10.5152/tjg.2025.25331. Cite this article as: Zhang H, Wang H, Tang W, Wu Y. The effect of dexmedetomidine on mortality in patients with acute pancreatitis: a retrospective propensity score matching analysis. Turk J Gastroenterol. Published online November 11, 2025. doi:10.5152/tjg.2025.25331.